2016
DOI: 10.1534/genetics.116.188367
|View full text |Cite
|
Sign up to set email alerts
|

Nonautonomous Roles of MAB-5/Hox and the Secreted Basement Membrane Molecule SPON-1/F-Spondin in Caenorhabditis elegans Neuronal Migration

Abstract: Nervous system development and circuit formation requires neurons to migrate from their birthplaces to specific destinations.Migrating neurons detect extracellular cues that provide guidance information. In Caenorhabditis elegans, the Q right (QR) and Q left (QL) neuroblast descendants migrate long distances in opposite directions. The Hox gene lin-39 cell autonomously promotes anterior QR descendant migration, and mab-5/Hox cell autonomously promotes posterior QL descendant migration. Here we describe a nonau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…While the transmembrane receptors UNC-40/DCC and PTP-3/LAR act as guidance receptors in Q cells, no extracellular factor has been identified that controls the direction of Q migration. Body wall muscle cells produce SPON-1/F-spondin and a signal dependent upon NFM-1/Merlin, both of which control the protrusive ability of the Q cells but do not affect direction [ 12 , 13 ]. Wnt ligands control Q descendant migrations [ 14 , 15 , 16 ] but do not apparently affect initial Q protrusion and migration.…”
Section: Introductionmentioning
confidence: 99%
“…While the transmembrane receptors UNC-40/DCC and PTP-3/LAR act as guidance receptors in Q cells, no extracellular factor has been identified that controls the direction of Q migration. Body wall muscle cells produce SPON-1/F-spondin and a signal dependent upon NFM-1/Merlin, both of which control the protrusive ability of the Q cells but do not affect direction [ 12 , 13 ]. Wnt ligands control Q descendant migrations [ 14 , 15 , 16 ] but do not apparently affect initial Q protrusion and migration.…”
Section: Introductionmentioning
confidence: 99%
“…Our combined results here suggest that NFM-1 and SLT-1 might act in the body wall muscles and/or anal sphincter muscle. Of note, the Q-cell protrusions are in close proximity to body wall muscles (Figure 6), and the posterior body wall muscles are the source of SPON-1/ F-spondin, which is involved in Q migrations (Josephson et al 2016b). Possibly, the posterior body wall muscles surrounding the Q neuroblasts serve as a source for cues that promote and guide their migrations.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous molecules have been identified that act in the Q cells to promote migration, such as the transmembrane receptors UNC-40/DCC, PTP-3/ LAR, and MIG-13 (Sundararajan and Lundquist 2012;Wang et al 2013;Sundararajan et al 2015), fewer have been identified that act outside the Q cells to control their migration. Of the nonautonomous genes that have been implicated in Q-descendant migration, most are secreted molecules such as Wnts (Hunter et al 1999;Whangbo and Kenyon 1999;Korswagen 2002;Pan et al 2006) and SPON-1/F-spondin (Josephson et al 2016b), although the Fat-like cadherin CDH-4 has been demonstrated to nonautonomously affect Q-cell migration (Sundararajan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…2016a), they do not control initial direction of Q migration. SPON-1/F-spondin and a signal produced in muscles by NFM-1/Merlin that interacts with SLT-1/Slit control the ability of Q cells to migrate, but are not involved in direction of migration (J osephson et al . 2016b; J osephson et al .…”
Section: Discussionmentioning
confidence: 99%
“…While the transmembrane receptors UNC-40/DCC and PTP-3/LAR act in Q cells as guidance receptors, no extracellular factor has been identified that controls the direction of Q migration. Body wall muscle cells produce SPON-1/F-spondin and a signal dependent upon NFM-1/Merlin, both of which control the protrusive ability of the Q cells but do not affect direction (J osephson et al . 2016b; J osephson et al .…”
Section: Introductionmentioning
confidence: 99%